Revolution as a Necessary Means of Social Change Reflected In Suzanne Collins The Hunger Games Trilogy: A Marxist Approach - Widiyanti, Nanik; , Dr. M. Thoyibi; , Nur Hidayat, M. Pd (2016)
The aims of this research are (1) to identify the characteristics of revolution at Suzanne Collins's The Hunger Games Trilogy, (2) to analyze the process of revolution at Suzanne Collins's The Hunger Games Trilogy, and (3) to reveal underlying concept of Suzanne Collins's thought about revolution at The Hunger Games Trilogy. The researcher uses descriptive qualitative research because there is no calculating data in this research. The qualitative research are describing data and not using any statistic procedure, and the researcher do not set hypothesis, and test it but focus on analyzing after taking the data. The researcher gets the data from the novels includes the narration, monologue, and dialogue. The techniques of collecting data are reading the data repeatedly, taking notes, underlying the important words, arranging the data, selecting the data, and drawing conclusion. The technique of data analysis is descriptive interactive which comprises three procedures, namely: data reduction, data display, and conclusion. The results of this research show: (1) The characteristics of revolution reflected in The Hunger Games Trilogy, (2) The process of revolution in The Hunger Games Trilogy, and (3) The concept of Suzanne Collins's thought about revolution. Key words: revolution, Suzanne Collins, The Hunger Games Trilogy, Marxist.